Computer vision for driving support systems: automatic traffic signs detection and proximity analysis - Aldwihe, Ramez (2018)
The future of the automotive industry in the coming years will depend heavily on artificial intelligence techniques. This thesis proposes a technique for automatic detection and recognition of traffic signs from images, to provide a driver alert system. The system developed in this work includes algorithms to detect, classify and recognize traffic signs, based on a set belonging to a German database. The main signs are circular and triangular, which have two different colors, namely red and blue. Several examples of images, in different scenarios, are taken from the German roads, and are used to test the effectiveness of the proposed system. Traffic signs are detected by analyzing the color and shape information. The detected signs are classified accordingtotheCNNMachineLearningtechnique,andcanbeclassifiedinto43differentclassesaccording to previous classification already existing in the reference database. After detecting the presence of a traffic signs, the traffic signs is detected by comparing the traffic signs detected in the images with the signs in the database. The overall recognition accuracy is 75 % and processing is normally done in 1.6 seconds. This project is implemented with the OpenCV tool and the Python programming language; Sumário: Visão Computacional aplicada a sistemas de apoio à condução: deteção automática de sinalização de trânsito e análise de proximidade O futuro da indústria automóvel nos próximos anos irá depender fortemente das técnicas de inteligência artificial. Esta tese propõe uma técnica para a deteção automática e o reconhecimento de sinais de trânsito a partir de imagens, para proporcionar um sistema de alerta ao condutor. O sistema desenvolvido neste trabalho inclui algoritmos para detetar, classificar e reconhecer sinais de trânsito, nomeadamente um conjunto pertencente a uma base de dados alemã. Osprincipaissinaissãocircularesetriangulares,osquaistêmduascoresdiferentes,nomeadamentevermelho e azul. Vários exemplos de imagens, em diferentes cenários, são tirados das estradas alemãs, e são usados para testar a eficácia do sistema proposto. Os sinais de trânsito são detetados analisando a informação de cor e forma. Os sinais detetados são classificadosapartirdatécnicaCNNMachineLearning, podendoserclassificadosem43classesdiferentes, de acordo com classificação prévia já existente na base de dados de referência. Após deteção da presença de um sinal de trânsito, o reconhecimento do mesmo é feito comparando os sinais de trânsito detetados nas imagens com os sinais existentes na base de dados. Oacertodoreconhecimentogeraléde75%eoprocessamentoéfeitonormalmenteem1.6segundos. Este projeto for implementado com a ferramenta OpenCV e a linguagem de programação Python.